Early Use of Echocardiography in Patients With Acute Pulmonary Embolism: Findings From the RIETE Registry - Behnood Bikdeli; José Luis Lobo; David Jiménez; Philip Green; Carmen Fernández‐Capitán; Alessandra Bura‐Riviere; Remedios Otero; Marco R. DiTullio; Silvia Galindo; Martin Ellis; Sahil A. Parikh; Manuel Monreal (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Transthoracic echocardiography (TTE) is often considered for risk stratification of patients with acute pulmonary embolism (PE). We sought to determine the contemporary utilization of early TTE (within 72 hours of PE diagnosis) and explored the association between TTE findings and PE‐related mortality. Methods and Results Data from the RIETE (Registro Informatizado Enfermedad TromboEmbolica) registry, a multicenter registry of consecutive patients with acute PE, were used (2001–July 2017). We used a generalized linear mixed model to determine predictors of early TTE performance. Moreover, the association between 3 TTE variables (right atrial enlargement, right ventricular hypokinesis, and presence of right heart thrombi) and 30‐day PE‐related mortality was assessed in generalized linear mixed models adjusted for PE severity index, and other comorbidities. Among 35 935 enrollees with acute PE, 15 375 (42.8%) underwent early TTE. There was an increase in early TTE utilization rate over time (P<0.001 for trend). Younger age, female sex, enrollment in countries other than Spain, history of coronary disease, heart failure, atrial fibrillation, tachycardia, and hypotension were the main predictors of early TTE (P<0.01 for all). In multivariable analyses, right atrial enlargement (adjusted odds ratio: 3.74; 95% confidence interval, 2.10–6.66), right ventricular hypokinesis (adjusted odds ratio: 3.11, 95% confidence interval: 1.85–5.21) and right heart thrombi (adjusted odds ratio: 4.39, 95% confidence interval, 1.99–9.71) were associated with increased odds for PE‐related mortality. Conclusions Early TTE is commonly performed for acute PE and utilization rates have increased over time. Right atrial enlargement, right ventricular hypokinesis, and right heart thrombi are predictive of worse outcomes. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT02832245.